Verbal memory dysfunction in substance use and gambling addictive disorders: a comparative analysis of performance accuracy and error typologies - Crivelli, Davide; Losasso, Doriana; Riccardi, Simona; Scaramuzzino, Maria Francesca; Zita, Gianmaria; Balconi, Michela (Frontiers in Psychology, 2025)
Addiction is increasingly recognized as a disorder involving not only reward dysregulation but also alterations in core cognitive processes, including learning and memory. Although various studies have documented memory impairments in substance use and behavioral addictions, evidence remains inconsistent—particularly regarding verbal memory deficits and the diagnostic relevance of specific recall error types. This study investigated immediate and delayed verbal memory performance and error patterns in 515 individuals, including patients with stimulant use disorder, alcohol use disorder, cannabis use disorder, or gambling disorder, and a healthy control group. Participants completed a digitized neurocognitive screening battery, which provided not only global performance indices but also specific error metrics. ANCOVA models controlling for age and sex revealed significantly lower correct recall scores in stimulant, alcohol, and gambling disorder groups compared to controls, across immediate and delayed trials. Alcohol use disorder was associated with elevated intrusion errors—suggesting inhibitory and interference suppression deficits—while stimulant use was linked to increased repetition errors—suggesting impaired monitoring and impulsive retrieval. Gambling disorder mirrored the overall performance decline of substance-related disorders but did not exhibit elevated error rates, pointing to a partially distinct cognitive profile. These findings highlight the value of combining global performance measures with qualitative error analysis in the assessment of memory function in addiction. By differentiating between types of recall errors, clinicians may better identify disorder-specific cognitive signatures, supporting more refined diagnostics and intervention strategies. The results further support the applicability of advanced neurocognitive tools for neuropsychological assessment in psychiatry.